“Efectos de la aplicación de fertilizantes ecológicos sobre el rendimiento del cultivo de arroz (Oryza sativa L.)”. - Dávila Hidalgo, Stalin Alexander (2018)
VIII. SUMMARY The present experimental work was established on the land owned by Mr. Robinson Roberto Dávila Saltos, located on the Babahoyo-San Juan route, 500 m from the Caracol road, in front of the "San José" Bananera, between the geographic coordinates of 110597.97 UTM south latitude and 277438.26 UTM west longitude, with a height of 8 masl The zone presents a humid tropical climate, with an average temperature of 25.60 ° C; an annual precipitation of 2298.8 mm, humidity 82% and 998.2 hours of annual average heliophany. Seeds of rice, variety SFL11 were used as seed material. The treatments were constituted by the different doses of ecological nutritional fertilizers such as Robusterra in doses of 0.5 and 1.0 kg / ha; Huminrich doses of 0.5 and 1.0 kg / ha; Germinox 20 in doses of 1.5 and 3.0 L / ha plus a control treatment without application of the product. The experimental design of Complete Blocks at Random was used with seven treatments and four repetitions, the test of significance used was Tukey at 95% probability. All the necessary agricultural work in rice cultivation was carried out for its normal development as land preparation, sowing, irrigation, fertilization, weed control, phytosanitary control and harvest. To estimate the effects of the treatments, the following data were taken: flowering days, plant height, number of tillers and panicles, length of the panicles, grains per panicles, weight of 1000 grains, grain yield and economic analysis. Based on the results obtained, it was determined that the application of ecological fertilizers had positive effects on the yield of rice cultivation, variety SFL11; the control treatment took time to flower, so the importance of applying ecological fertilizers is reflected; the agronomic characteristics such as plant height, tillers and panicles / m2, length of panicles and grains per spike stood out when Huminrich was applied at a dose of 0.5 kg / ha and the weight of 1000 grains, yield and economic analysis reached higher averages using Huminrich ecological fertilizer in doses of 0.5 kg / ha, with a net profit of $ 304.41 Key words: ecological fertilizers, rice, yield, Robusterra, Huminrich, Germinox 20.